2022
DOI: 10.3390/genes13060975
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification Role of Metabolic Glutathione S-Transferase (GST) Genes in Blood Lead Concentrations of Jamaican Children with and without Autism Spectrum Disorder

Abstract: Glutathione S-transferases (GST) are involved in the detoxification of exogenous chemicals including lead (Pb). Using data from 344 pairs of autism spectrum disorder (ASD) cases and age- and sex-matched typically developing (TD) controls (2–8 years old) from Jamaica, we investigated the interaction between three GST genes and ASD status as determinants of blood Pb concentrations (BPbCs). We found that ASD cases had lower geometric mean BPbCs than TD children (1.74 vs. 2.27 µg/dL, p < 0.01). Using a co-domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The concept of “interaction” has been construed in many ways through different scientific fields . For example, in epidemiological studies, interactions are usually reported through association estimates of their effect sizes or inclusion probabilities. Though estimating associations is essential, most methods do not provide any mechanistic or biological insight, possibly because the reported interactions are of particular functional forms (for example, multiplication of exposures) rather than representing their collective activities beyond certain concentration thresholds . Further, after applying certain dimension reductions, most interactions are reported between sets of reduced exposures, limiting interpretability.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of “interaction” has been construed in many ways through different scientific fields . For example, in epidemiological studies, interactions are usually reported through association estimates of their effect sizes or inclusion probabilities. Though estimating associations is essential, most methods do not provide any mechanistic or biological insight, possibly because the reported interactions are of particular functional forms (for example, multiplication of exposures) rather than representing their collective activities beyond certain concentration thresholds . Further, after applying certain dimension reductions, most interactions are reported between sets of reduced exposures, limiting interpretability.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of "interaction" has been construed in many ways through different scientific fields 21 . For example, in current epidemiological studies, interactions are usually reported through association estimates of their effect sizes or inclusion probabilities [22][23][24][25][26][27][28][29][30][31][32][33] . Though estimating associations is essential, most methods do not provide any mechanistic or biological insight, possibly because the reported interactions are of particular functional forms (for example, multiplication of exposures) rather than representing their collective activities beyond certain concentration thresholds 34 .…”
Section: Introductionmentioning
confidence: 99%